Spatial distribution of Tetraclinis articulata (Vahl) Mast. formations in north- western Algeria - El Mechri, Omar; Belgherbi, Benamar; Benaradj, Abdelkrim; Berkane, Ibrahim (Biodiversity: Research and Conservation, 2024)
Tetraclinis articulata (Vahl) Mast., syn. Thuja articulata Vahl, is mainly confined to the south-western Mediterranean region and considered to be endemic to North Africa (Morocco, Algeria, and Tunisia). This tree species is experiencing a significant regression of its range, in some cases irreversible. Currently, it is classified as an Ibero-Mauritanianelement. Our objective was to study the dynamics of land cover and even the possibilities of rehabilitation of this species. The forest formation based on Tetraclinis articulata, represented in this study by the areas known as Oued Fergoug and Béni-Khenies forests, has been subject to both regressive and progressive dynamics. An analysis and mapping of the vegetation over 48 years (1975-1994-2022) revealed that the forest cover, with an initial surface area of 3680.47 ha (61.36%) deteriorated dramatically in 1994 as a result of repeated fires and the drought that prevailed then, to 122.65 ha (2.04%) – a truly alarming situation. However, in 1994-2022 this forest formation experienced a significant biological recovery, so that the estimated vegetation cover is now 4292.64 ha (71.56%), with the appearance of dense woodland in an area of 13.18 ha.